Metaphorical perceptions of gifted and normally developing students on the concept of solving mathematical problems - Er, Zübeyde; Dinç Artut, Perihan (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
This research aims to determine the metaphorical perceptions of gifted and normally developing students attending primary education regarding solving mathematical problems. In the research, the qualitative research method was employed. In the 2022-2023 academic year, 206 students studying at the primary school level in Turkey were determined according to the convenience sampling method. Students were given a sentence such as “In my opinion, solving mathematical problems is like .........., because; ........” and they were asked to develop a metaphor about mathematical problem solving and explain their reasoning. The research data were categorized using qualitative data analysis methods, and content analysis was performed. In addition, the categories related to the metaphors created and the distribution of the students according to their gender, whether they are gifted or not, and gender were analyzed. From the analysis of the data, seven categories and 84 metaphors emerged. As a result of the data analysis showed that male students were more likely than female students, and gifted students were more likely to produce metaphors than students with normal development. In the seven conceptual categories for mathematical problem solving, 37 metaphors were developed in the conceptual category containing positivity, 16 in the conceptual category containing negativity, and 8 in the conceptual categories containing and developing necessity. Besides, it was seen that 15 metaphors were developed in conceptual categories of Drug Therapeutic, Goal or Result Attainment, Nature, and Natural Phenomena.